Prevalence of central line associated blood stream infection (CRBSI) and catheter colonization in ICU settings of a tertiary care hospital in sub Himalayan region - Nidhi Negi; Suchandra Gupta; Iva Chandola; Vijay Kataria (Tropical Journal of Pathology and Microbiology, 2019)
Background: Catheter-related bloodstream infections (CRBSIs) are one of the major causes of morbidity and mortality in critically ill hospitalized patients mainly in ICU settings. Emergence of multidrug resistant bacteria makes it compulsory to know the current sensitivity profile of the organism against antimicrobial agents.Objective: To isolate the etiological agents responsible for CRBSI and to find out the spectrum of antimicrobial sensitivity of isolated organisms.Material and Methods: A total of 180 suspected cases of CRBSI were included in the study in which 44 (24.44%) cases were positive for catheter tip colonization. Further isolation was done using standard laboratory procedures.Result: Out of a total of 180 suspected cases of CRBSI 44 cases were found to be positive for catheter tip colonization after which they were divided into two groups 4 (2.2%) had CRBSI while 40 (22.22%) had local catheter infections.Conclusion: Catheter colonization and duration of catheterization has an important role in development of CRBSI which may lead to septicaemia and multi-organ failure. CRBSI must be suspected in the catheterized patient having sign and symptoms of septicaemia.